The Role of Human Resources Management Strategies in Organizational Excellence: An Applied Study on Employees of the Human Resources Development Fund in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2024)
This study aimed to examine the impact of human resource management strategies, including job analysis, human resource planning, training, performance evaluation, and compensation, on achieving organizational excellence in its various dimensions such as leadership excellence, strategic excellence, organizational structure excellence, individual excellence, and organizational culture excellence at the Human Resources Development Fund in the Kingdom of Saudi Arabia. The study sample consisted of 262 employees out of a total of 578, and the study followed a descriptive-analytical approach, utilizing the SPSS program for data analysis. The study found statistically significant evidence of the impact of human resource management strategies on achieving organizational excellence at the Human Resources Development Fund in the Kingdom of Saudi Arabia. The study recommended the continuous development of effective and well-thought-out human resource management strategies, covering all stages of the employee lifecycle, to optimize the utilization of human resources and achieve organizational performance and objectives.
Keywords: Human Resource Management Strategies; Organizational Excellence; Human Resources Development Fund in the Kingdom of Saudi Arabia